O programa Escola de Hackers e sua contribuição para o desenvolvimento do raciocínio lógico em crianças do Ensino Fundamental II - Giaretta, Milene (2018)
The present work belongs to the line of research: Information technologies, communication and interaction applied to the teaching of Sciences and Mathematics, of the Programa de Pós Graduação em Ensino de Ciências e Matemática (Post-Graduate Program in Teaching Sciences and Mathematics). Its purpose is to provide a distinguished space for the development of computer programming and logical reasoning skills, since technology has revolutionized not only the way we live but also how we learn, with the provision of an ample amount of digital resources developed specifically to support the process of teaching learning, targeting those educators who wish to make their classes more interesting, attractive and interactive. Among the available resources, it is worth mentioning the teaching of programming, an important element in the formation of the individual, considering the possibility of allying technology and education, approaching the Programa Escola de Hackers (School of Hackers Program), which seeks to provide a space for the development of knowledge of diverse areas through the programming of computers for primary school students. The project, already applied with satisfactory results in relation to the development and improvement of the cognitive abilities of the participants, is based on a didactic book structured through problem solving and challenges, aiming at the usage of the Scratch software. Therefore, this work proposes to adapt the didactic material from Bloom Taxonomy perspectives, since it is geared towards educational formation and has the objective of learning directed to the improvement in cognitive development. Thus, teaching is not centralized in the transfer of content and seeks the expressive amplification of the results obtained previously, to then store the data in a blog, which will be developed in the form of teacher support material. In this sense, answers are sought for the following question: What are the characteristics and consequences of a teaching process of computer programming for elementary school students for the development of logical reasoning? In this cybernetic context, it is understood that to literate individuals digitally, so that they learn to transit through the digital world and to use technology in a qualified way, is also a function of the school. The educational product, which accompanies this dissertation, is available in digital format for free access on the Educapes portal at the following address: <http://educapes.capes.gov.br/handle/capes/431416>.